2020
DOI: 10.1097/pec.0000000000002057
|View full text |Cite
|
Sign up to set email alerts
|

Access to Outpatient Pediatric Mental Health Care After Emergency Department Discharge

Abstract: Objectives: Pediatric mental health presentations to emergency departments (EDs) have shown dramatic increases nationally. This study aimed to identify the ability of patients discharged with mental health from the ED to establish outpatient care.Methods: This was a cross-sectional study of all mental health patients aged 7 to 19 years who were seen by a child psychiatry consult team in a tertiary care pediatric ED from September 2016 to January 2017. Patients were contacted by phone at least 6 months after di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…These include increasing primary care utilization, transferring care for boarding patients to inpatient teams, increasing the care provided in triage, and creating alternative care sites for seeing patients. [18][19][20][21] Alternative care sites are spaces temporarily converted for health care delivery to provide additional capacity and capability. 22 In the case of the ED, alterative care site refers to a space converted for clinical use outside of the main ED where care is provided by the ED staff.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include increasing primary care utilization, transferring care for boarding patients to inpatient teams, increasing the care provided in triage, and creating alternative care sites for seeing patients. [18][19][20][21] Alternative care sites are spaces temporarily converted for health care delivery to provide additional capacity and capability. 22 In the case of the ED, alterative care site refers to a space converted for clinical use outside of the main ED where care is provided by the ED staff.…”
Section: Introductionmentioning
confidence: 99%
“…While patient volumes and mix do not change abruptly, they eventually reach a threshold that prompts pediatric EDs to innovate clinical operations models in response. These include increasing primary care utilization, transferring care for boarding patients to inpatient teams, increasing the care provided in triage, and creating alternative care sites for seeing patients 18–21 . Alternative care sites are spaces temporarily converted for health care delivery to provide additional capacity and capability 22 .…”
Section: Introductionmentioning
confidence: 99%
“…13 A significant barrier to implementing these models includes the scarcity of certain mental health resources in the ED, the challenge of establishing safe disposition with efficiency, and outpatient mental health management. 2 One study by Sheridan et al 14 reported that although the majority of patients are evaluated by mental health specialists within 1 month of discharge, almost 10% of patients never establish continuing mental health care.…”
mentioning
confidence: 99%
“…9 Furthermore, providers in the ED report complex barriers to addressing suicidality in the ED setting and generally apply a biomedical model for treating suicidal patients with limited continuity of care. 10,11 In addition to potentially distressing patient and provider experiences, suicide evaluations in a general ED present financial and time burdens to both the patient and the medical center. Estimates of the national cost of suicide in the United States range from 44.7 billion to 93.5 billion US dollars, 12,13 and EDs across the United States report over 500,000 visits with chief complaint of suicidality, although this is not specific to pediatric ED visits.…”
mentioning
confidence: 99%